2020
DOI: 10.1021/acs.accounts.0c00103
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Occlusion of Nanoparticles within Inorganic Single Crystals

Abstract: This is a repository copy of Efficient occlusion of nanoparticles within inorganic single crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 50 publications
0
35
0
Order By: Relevance
“…Clearly, this Fe 3 O 4 encapsulation occurred during the copolymerization of hexachlorocyclotriphosphazene and 4,4′‐sulfonyldiphenol. It might be worth noting that Ning et al recently reported that polymeric or inorganic nanoparticles with proper surface functionality could also be efficiently incorporated into inorganic crystal hosts 53–57 . X‐ray diffraction (XRD) results showed that Fe 3 O 4 nanoparticles and Fe 3 O 4 @PZS@HMP 1 exhibited same pattern (ESI†, Figure S1d).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Clearly, this Fe 3 O 4 encapsulation occurred during the copolymerization of hexachlorocyclotriphosphazene and 4,4′‐sulfonyldiphenol. It might be worth noting that Ning et al recently reported that polymeric or inorganic nanoparticles with proper surface functionality could also be efficiently incorporated into inorganic crystal hosts 53–57 . X‐ray diffraction (XRD) results showed that Fe 3 O 4 nanoparticles and Fe 3 O 4 @PZS@HMP 1 exhibited same pattern (ESI†, Figure S1d).…”
Section: Resultsmentioning
confidence: 90%
“…It might be worth noting that Ning et al recently reported that polymeric or inorganic nanoparticles with proper surface functionality could also be efficiently incorporated into inorganic crystal hosts. [53][54][55][56][57] X-ray diffraction (XRD) results showed that Fe 3 O 4 nanoparticles and Fe 3 O 4 @PZS@HMP 1 exhibited same pattern (ESI †, Figure S1d). The synthesized Fe 3 O 4 @PZS@HMP 1 particles can be dispersed well in tetrahydrofuran, toluene, dichloromethane, and chloroform.…”
Section: Resultsmentioning
confidence: 99%
“…Up to the moment of preparing this article there have been more than 20 review articles published on RAFT‐mediated PISA, looking into different aspects of the technique. [ 72,76–85 ] Only in 2020 (by September) there have been more than 100 papers published on the topic. Here we focus mainly on the latest and the most outstanding reports on RAFT‐PISA prepared nano‐objects.…”
Section: Novel Developments In Raft Processmentioning
confidence: 99%
“…Polymers prepared by RAFT have been used in many different fields, notably in preparation of biomaterials (implants, scaffolds, coatings, drug, gene delivery, etc. ), [ 226–230 ] sensing and detection, [ 231,232 ] coatings and patterning, [ 233–235 ] electronics, [236] nanocomposite, [ 235,237–240 ] and vitrimers. [ 241 ] One of the most recent and emerging applications of polymers and nanoparticles prepared by RAFT is membranes for separation.…”
Section: Novel Applications Of Raftmentioning
confidence: 99%
“…At first sight, nanoparticle occlusion within inorganic crystals appears to be highly counter-intuitive because crystallization is normally considered to involve expulsion of impurities,r ather than their incorporation. Nevertheless, efficient nanoparticle occlusion can occur under optimized conditions, [1] producing nanocomposite crystals that differ significantly from those hybrid materials produced via conventional chemical or mechanical mixing. [2] In some cases, such nanocomposite crystals can exhibit enhanced hardness and toughness compared to their geological counterparts.…”
Section: Introductionmentioning
confidence: 99%